The co-presence of high-risk human papillomaviruses and Epstein-Barr virus is linked with tumor grade and stage in Qatari women with breast cancer. Issue 4 (3rd April 2021) - Gupta, Ishita; Jabeen, Ayesha; Al-Sarraf, Reem; Farghaly, Hanan; Vranic, Semir; Sultan, Ali A.; Al Moustafa, Ala-Eddin; Al-Thawadi, Hamda
ABSTRACT: High-risk human papillomaviruses (HPV) can be present and cooperate with Epstein–Barr virus (EBV) to promote the onset and/or progression of various cancers including cervical, breast, head and neck as well as colorectal. In this investigation, we explored the co-prevalence of high-risk HPV and EBV in 74 breast cancer tissues from Qatari women using polymerase chain reaction. We found that high-risk HPV and EBV are present in 48/74 (65%) and 36/74 (49%) of the cases, respectively. While we noted that the presence of HPV presence is associated with triple-negative breast cancer (TNBC) ( p = .008), however, the presence of EBV did not correlate with any breast cancer subgroup. Moreover, our data revealed that high-risk HPV and EBV are co-present in 35/74 (47%) of the samples and their co-presence is significantly associated with tumor grade ( p = .04) and tumor stage ( p = .04). These data indicate that HPV and EBV are commonly co-present in breast cancer and their association could be linked with a more aggressive tumor phenotype. Thus, further investigations are essential to understand the underlying mechanisms of HPV and EBV cooperation in breast carcinogenesis.